Inventori Kepribadian Ideal Budaya Dayak Ngaju dalam Layanan Bimbingan dan Konseling - Heriansyah, Masnurrima (STKIP Muhammadiyah Pringsewu, 2017)
Abstract: This research was intended to generate ideal personality inventory of high school students with Dayak Ngaju cultural background. The subjects of this study were students SMA Negeri 1 dan 2 Palangkaraya for about 60 students, the subject collecting using purposive sampling technique. A research design that used in the research development of ideal personality inventory of Dayak Ngaju culture in guidance and counseling services were mixed methods design. The validity of ideal personality inventory of Dayak Ngaju culture in guidance and counseling services were obtained from experts judgments and Item-Test Correlation using Product Moment Pearson correlation analysis while the reliability was obtained by counting the Alpha coefficient through the Cronbachs Alpha reliability analysis. The result of this research was to generate ideal personality inventory of Dayak Ngaju culture in guidance and counseling services which consisting of 42 items statement that is 25 items favorable and 17 items unfavorable after taking experts judgments, small clusters and large clusters test. Drawing conclusions of the study after taking 2 times test generated 42 valid items with the coefficients reliability of 0,778 so the level of validity and reliability considered high.Keywords: Dayak ngaju, Inventory, Personality